Pengembangan Modul Matematika sebagai Penunjang Pembelajaran secara Online untuk Siswa SMK yang Melaksanakan Prakerin (Praktek Kerja Industri) - Sri Rahayu; Bunga Ayu Wulandari; Muhammad Ali (Universitas Batanghari Jambi, 2023)
This study aims to produce a Mathematics Module to Support Online Learning for Vocational High School Students Carrying Out Internships (Industrial Work Practice). This research is development research, with the research design used is Research and Development (R&D) with the ADDIE model (Analyze, Design, Development, Implementation, Evaluation) which consists of five stages, namely the analysis stage, design stage, development stage, implementation stage and evaluation stage. The subjects of this study were 20-30 students of class XI Automotive Light Vehicle Engineering at Setih Setio 1 Muara Bungo Vocational School. The procedure for this research was preliminary research, designing modules, preparing instruments, expert tests, individual tests, and student tests. The feasibility of this product is seen from the results of expert validation by achieving the appropriate criteria for the module. Research results based on the assessment of material experts in the very feasible category, and the media expert's assessment in the very feasible category, the assessment of students on small-scale tests and large-scale tests gave an average percentage of positive responses. Based on the assessment of material experts, media experts, design experts, student responses, it can be concluded that the mathematics module with statistics material is appropriate for use as a support for SMK students who carry out Internship (Industrial Work Practice).